2011
DOI: 10.1007/s00223-011-9511-3
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Tolerability and Patterns of Switching in Patients Treated for Primary Osteoporosis: The Swedish Adherence Register Analysis (SARA)

Abstract: The objective of this study was to describe and analyze the gastrointestinal tolerability and medication switching in patients receiving treatment for primary osteoporosis in Sweden. The study was based on all patients starting therapy with alendronate, risedronate, strontium ranelate, and raloxifene in Sweden between 2005 and 2009. The primary outcome measure was start of treatment with a gastroprotective agent, and the secondary outcome was hospitalization for a gastrointestinal adverse event (GIAE). Switchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The results of the present meta-analysis are consistent with those from previous studies (28)(29)(30)(31)(32)(33)(34)(35)(36), which also observed no significant difference in the frequency of upper GIAEs between placebo-treated and Aln-treated groups, and demonstrated that the GI safety and tolerability profile of Aln resembles the placebo (10,11). However, the present results contradict a previous study that suggested that Aln treatment may be associated with an increased risk of upper GIAEs in patients, as compared with no treatment (17). Furthermore, in the present study, the incidences of the primary individual upper GIAEs, including abdominal pain, nausea, dyspepsia, acid regurgitation, vomiting, gastroesophageal reflux and esophagitis, were not significantly different between the placebo-and Aln-treated groups.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The results of the present meta-analysis are consistent with those from previous studies (28)(29)(30)(31)(32)(33)(34)(35)(36), which also observed no significant difference in the frequency of upper GIAEs between placebo-treated and Aln-treated groups, and demonstrated that the GI safety and tolerability profile of Aln resembles the placebo (10,11). However, the present results contradict a previous study that suggested that Aln treatment may be associated with an increased risk of upper GIAEs in patients, as compared with no treatment (17). Furthermore, in the present study, the incidences of the primary individual upper GIAEs, including abdominal pain, nausea, dyspepsia, acid regurgitation, vomiting, gastroesophageal reflux and esophagitis, were not significantly different between the placebo-and Aln-treated groups.…”
Section: Resultssupporting
confidence: 88%
“…Previous studies have demonstrated that Aln is able to effectively reduce the risk of vertebral, non-vertebral, hip and wrist fractures (7)(8)(9). The safety and tolerability of Aln has previously been investigated in various randomized controlled trials (RCTs) and retrospective studies (10)(11)(12)(13)(14)(15)(16)(17)(18), and the majority of these have reported similar side effects, including gastrointestinal tract adverse events (GIAEs), for the Aln-treated and placebo-treated groups. It has been reported that oral administration of bisphosphonates, particularly those containing a nitrogen atom, may be accompanied by digestive tract disturbances (19).…”
Section: Introductionmentioning
confidence: 99%
“…Such events, or use of medications suggesting their occurrence, have been shown to be associated with reduced adherence (both compliance and persistence) to treatment [611] and low treatment satisfaction [1214]. Increased health care resource use has also been documented among patients with osteoporosis treatment-related GI events [15, 16]. However, such associations have not been assessed in Asian or Australian populations.…”
Section: Introductionmentioning
confidence: 99%